Inflation expectations in the wake of the war in Ukraine - Geghetsik Afunts; Misina Cato; Tobias Schmidt (Deutsche Bundesbank, 2023)
Russia's invasion of Ukraine is posing a range of new challenges to the global economy, including affecting the inflation expectations of individuals. In this paper, we aim to quantify the effect of the invasion on short- and long-term inflation expectations of individuals in Germany. We use microdata from the Bundesbank Online Panel - Households (BOP-HH), for the period from February 15th to March 29th, 2022. Treating the unanticipated start of the war in Ukraine on the 24 th of February 2022 as a natural experiment, we find that both short- and long-term inflation expectations increased as an immediate result of the invasion. Long-term inflation expectations increased by around 0.4 percentage points, while the impact on short-term inflation expectations was more than twice as large - around one percentage point. Looking into the possible mechanisms of this increase, we suggest that it can be partially attributed to individuals' fears of soaring energy prices and increasing pessimism about economic trends in general. Our results indicate that large economic shocks can have a substantial impact on both short and long-term inflation expectations.
Keywords: D84; D12; E3; 330; inflation expectations; Russian invasion of Ukraine; survey; natural experiment